Assessment of protective immune response of inactivated equine herpesvirus–1vaccine in pregnant BALB/c mice - SINGH, B K; VIRMANI, NITIN; GULATI, BALDEV R (The Indian Journal of Animal Sciences, 2011)
To assess the immunogenic potential of inactivated equine herpesvirus–1 (EHV–1) vaccine in murine model, female BALB/c mice (group 1) were vaccinated intraperitoneally twice, 21 days apart, while group 2 mice were sham-inoculated and served as control. After immunization, antibodies against EHV–1 were detected on day 14, 21 and 28 day by virus neutralization test and enzyme-linked immunosorbent assay, but there was no significant increase in cell-mediated immune response. After mating and confirming pregnancy, the mice were challenged by intranasal instillation of 107.0 TCID50/25 μl of EHV–1 virus (Raj–98 strain) at day 14 of gestation. Following challenge, clinical signs, viz. dyspnoea, crouching in corners, vaginal discharge, abortion, and mortality increased significantly in non-vaccinated (group 2) mice with a clinical score of 8.17 as compared to vaccinated mice, where dyspnoea, crouching in corners and mortality were not observed and clinical score was 2.0 on day 3 post-challlenge. After challenge, vaccinated mice showed less number (30%) of abortions as compared to 66.66% in non-vaccinated mice. Reduced virus titre recovery and score for herpesvirus-specific pathology in maternal lungs were observed in vaccinated dams. Indirect immunoperoxidase staining of lung tissues of immunized dam demonstrated less viral antigen than in unimmunized dams. These results confirm that inactivated EHV–1 vaccine afforded good humoral immune response and partial protection in pregnant BALB/c mice.